Plasticity of the fatty acid whole blood lipidome in the progression of canine periodontal disease: a pilot study - Silva, Carolina; Sousa, Tiago; Pinho, Marisa; Fontes, Ana Carolina; Abrantes, Ana Carolina; Brancal, Hugo; Peixoto, Francisco; Domingues, Rosário; Viegas, Carlos (Frontiers in Veterinary Science, 2025)
IntroductionPeriodontal disease is a progressive infectious-inflammatory disease, and, in the case of dogs, it is one of the most frequently diagnosed pathologies. Fatty acids (FA) play a dual role in inflammatory processes, as they have anti-inflammatory and pro-inflammatory functions. The goals of this study were to compare the FA profiles of whole blood in dierent degrees of canine periodontal disease in a single breed, the Portuguese Podengo, and consequently, to analyze the possible variation of these FA with the progression of the disease.MethodsWhole blood FA values were determined in healthy dogs, dogs with gingivitis and dogs with periodontitis by gas-chromatography-mass spectrometry. The study sample included 10 dogs considered clinically healthy, 10 dogs with gingivitis and 9 dogs with periodontitis.ResultsArachidonic acid and omega-3 docosapentaenoic acid were significantly higher in periodontitis cases compared to the control group, but curiously the arachidic acid was lower in the gingivitis group compared to the control group. Total saturated FA was significantly lower in the periodontitis group compared to the control group, while the total polyunsaturated FA was significantly higher in gingivitis and periodontitis groups than in the control group. Omega-6 polyunsaturated FA was significantly higher in cases of periodontitis than in healthy dogs.DiscussionThe results presented suggest that the systemic impact of canine periodontal disease is partly reflected in the lipidomic profile of whole blood FA. The potential roles of the FA identified have important implications for a better understanding of the pathogenesis of canine periodontal disease, being equally endowed with potential as biomarkers for diagnosis and disease progression.